Different Origins of Newcastle Disease Virus Hemagglutinin-Neuraminidase Protein Modulate the Replication Efficiency and Pathogenicity of the Virus - Jin, Ji-hui; Cheng, Jin-long; He, Zi-rong; Ren, Ying-chao; Yu, Xiao-hui; Song, Yang; Yang, Hui-ming; Yang, Yan-ling; Liu, Tong; Zhang, Guo-zhong (Frontiers in Microbiology, 2017)
To investigate the exact effects of different origins of Newcastle disease virus (NDV) hemagglutinin-neuraminidase (HN) protein to the biological characteristics of the virus, we systematically studied the correlation between the HN protein and NDV virulence by exchanging the HN of velogenic or lentogenic NDV strains with the HN from other strains of different virulence. The results revealed that the rSG10 or rLaSota derivatives bearing the HN gene of other viruses exhibited decreased or increased hemadsorption (HAd), neuraminidase (NA) and fusion promotion activities. In vitro and in vivo tests further showed that changes in replication level, tissue tropism and virulence of the chimeric viruses were also consistent with these biological activities. These findings demonstrated that the balance among three biological activities caused variation in replication and pathogenicity of the virus, which was closely related to the origin of the HN protein. Our study highlights the importance of the HN glycoprotein in modulating the virulence of NDV and contributes to a more complete understanding of the virulence of NDV.